A composite desirability function-based modeling approach in predicting mass condensate flux of condenser in seawater greenhouse - Yetilmezsoy, Kaan; Abdul-Wahab, Sabah Ahmed (ELSEVIER SCIENCE BV, 2014)
The main aim of this paper was the development of a new empirical model based on the composite desirability function methodology for predicting mass condensate flux of a condenser in a seawater greenhouse located at Al-Hail, Muscat, Oman. The computational analyses were conducted for simulating relative humidity of inlet dry air, inlet temperature of humid air (dry bulb temperature), temperature of the seawater at the inlet, mass flow of humid air input, and mass flow of seawater at the inlet. The performance of the proposed empirical model was assessed by means of various descriptive statistical indicators. The comparison of the proposed approach with existing condensation data exhibits very good precision of the developed composite desirability function-based model in predicting the mass condensate flux for the condenser process. The proposed mathematical formulation eliminated the various complex variable interactions and many unit conversions usually carried out in the theoretical approach. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Desirability function; Empirical modeling; Mass condensate flux; Relative humidity; Seawater greenhouse; HUMIDIFICATION-DEHUMIDIFICATION DESALINATION; FRESH-WATER PRODUCTION; SIMULATION; PERFORMANCE; SYSTEMS; OPTIMIZATION; GENERATION; DESIGN; AREA; Engineering; Water Resources